Day 2 Thu, September 25, 2014 2014
DOI: 10.2118/171076-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Asphaltenes in Emulsion Formation for Steam Assisted Gravity Drainage (SAGD) and Expanding Solvent - SAGD (ES-SAGD)

Abstract: Steam Assisted Gravity Drainage (SAGD) and Expanding Solvent SAGD (ES-SAGD) have previously been compared and ES-SAGD has shown improved oil recovery with lower energy and water requirements and significant oil upgrading. However, solvent selection is the key factor which determines the performance of ES-SAGD due to the asphaltene-solvent interaction. The change in asphaltene stability with the solvent type can have several drawbacks during ES-SAGD. Stable emulsion formation is one of these problems which have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…This gas layer acts as a heat insulator and adversely impacts oil reduction. Similarly, Kar et al noted comparable enhancements in employing lighter solvents (C 6 ) combined with heavier toluene. This co-injection of both solvents resulted in increased recovery rates and reduced asphaltene content in the produced oil.…”
Section: Thermal Eorsupporting
confidence: 84%
“…This gas layer acts as a heat insulator and adversely impacts oil reduction. Similarly, Kar et al noted comparable enhancements in employing lighter solvents (C 6 ) combined with heavier toluene. This co-injection of both solvents resulted in increased recovery rates and reduced asphaltene content in the produced oil.…”
Section: Thermal Eorsupporting
confidence: 84%
“…Further, since the formation of emulsions result from steam condensate contacting oil near the boundary of the steam chamber (Mohammadzadeh et al, 2012;Zendehboudi et al, 2014;Kar et al, 2014), the role of emulsions on oil flow and solvent mass transfer also needs more study.…”
Section: Proposed Steam-solvent Injection Strategy To Improve Es-sagdmentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 14 It has been observed that both water and clay contribute the formation of stable emulsions. 13,19,41 The greatest water content (54 wt %) with the greatest clay content (14.25 wt %) is observed in the emulsions originated from E1 in which only steam was injected for 12 hours. In ES-SAGD experiments (E2, E3, and E4), the water content increase is observed with the increase in asphaltene content (compare Water Content in Figure 4-A to Asphaltenes in Figure 4 The asphaltene-water interaction shows a linear relation ( Figure 5).…”
Section: Resultsmentioning
confidence: 98%
“…It has been observed that both water and clay contribute to the formation of stable emulsions. ,, The greatest water content (54 wt %) with the greatest clay content (14.25 wt %) is observed in the emulsions that originated from E1, in which only steam was injected for 12 h. In ES-SAGD experiments (E2–E4), the water content increase is observed with the increase in asphaltene content. (Compare water content in Figure A to asphaltenes in Figure B.)…”
Section: Experimental Results and Discussionmentioning
confidence: 98%